Differences in triglyceride levels before and after whey protein intervention in field workers exposed and unexposed to arsenic - Rahmadhani, Eka Putri; Margawati, Ani; Kartini, Apoina (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2021)
Background: A work environment that is exposed to heavy metals, such as a coal mining environment, can change fat metabolism in the body. Changes in fat metabolism will lead to cardiovascular disease. Consumption of dairy products, e.g. whey protein, can reduce the risk of metabolic disorders and cardiovascular disease.Objectives: To test and analyze the differences in triglyceride levels before and after whey protein intervention to field workers with different working conditions.Materials and Methods: This experimental research with pretest and posttest was conducted on field workers at PT Bukit Asam Tbk. Tarahan Port Unit, Lampung as an Arsenic exposed group and PTPN VII Way Berulu Business Unit as an Arsenic unexposed group. Both groups received 24 grams of whey protein daily for 28 days. The triglyceride levels before and after the intervention were measured by laboratory analysis using the enzymatic calorimetry method. The data were analyzed using independent t-test, Mann Whitney test, and Wilcoxon test.Results: The average triglyceride levels increased by 50.48 Â± 98.09 mg/dL in the exposed group and 16.78 Â± 67.67 mg/dL in the unexposed group. There was a significant difference in triglyceride levels before and after the whey protein intervention in the two groups.Conclusions: The whey protein intervention increased the triglyceride level in the exposed group and decreased it in the unexposed group.